(untitled) (Bangladesh Rice Journal, 2021)
Using cross-sectional data obtained through carrying out a sample survey conducted during 2018, we examined the perception of farmers and millers about the paddy and rice procurement system and its feasibility. A probit model was employed to ascertain the factors influencing the likelihood of participating in the procurement system by farmers from two districts of Bangladesh. The results showed that the government procurement system has significant impacts on both the participant farmers and millers. The farmers and millers’ net profit was TK 4,205 and TK 3,930 by selling a ton of paddy and cleaned rice, respectively, to the procurement center rather than in the local market. The probit regression analysis revealed nine different factors that significantly influenced farmers’ participation in the paddy procurement programme. Results further implied that educated farmers had procurement cards with sufficient system knowledge, residing near the hub with improved road access, and association with political parties get preference in participating in the programme. The findings also indicate that lucrative prices, programme scheduling and good conduct of procurement employees inspire farmers to participate in the programme. The government procurement programme has several drawbacks such as anomalies in selecting farmers, taking extra paddy by the employees, corruption, unsuitable payment system, and procurement capacity. Therefore, the government would be vigilant to ensure that the procurement system will provide farmers with price support. A well-functioning procurement system is crucial for guaranteeing the country’s food security by ensuring a fair price for the producers. Finally, the study proposed some policy guidelines based on the findings to establish a sound paddy and/or rice procurement system in Bangladesh. Bangladesh Rice J. 24 (1): 31-46, 2020